A meta-analysis of business cycle correlation between the euro area and CEECs: What do we know - and who cares? - Jarko Fidrmuc; Iikka Korhonen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
We review the literature on business-cycle correlation between the euro area and Central and Eastern European countries (CEECs), a topic that has gained attention in recent years as new EU entrants prepare for participation in the monetary union.Our meta-analysis suggests several CEECs already have comparably high correlation with the euro area business cycle.We also find that estimation methodologies can have a significant effect on correlation coefficients.While central bankers are more conservative in their estimates, we find no evidence of a geographical bias in the studies.
URN:NBN:fi:bof-201408072118
Keywords: C42; E32; F15; F31; 330; monetary union; optimum currency area; business cycles; meta- analysis